Gratitude And Psychological Well-Being Of Students At Muhammadiyah University Of Sidoarjo During The Covid -19 Pandemic: Kebersyukuran Dengan Kesejahteraan Psikologis Mahasiswa Universitas Muhammadiyah Sidoarjo Pada Masa Pandemi Covid-19 - Afifah, Amalia Firda; Ansyah, Eko Hardi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the relationship between gratitude and the psychological well-being of students at Muhammadiyah University of Sidoarjo during the Covid-19 pandemic. This study uses a quantitative research method with a correlational approach and uses a scale measuring instrument, namely the gratitude scale and psychological well-being scale. The sample in this study was 337 students from a population of 9,591 students who were taken using incidental techniques, namely sampling based on coincidence or samples that were met or met by researchers by chance. Data analysis was performed using a gratitude scale and a psychological well-being scale using SPSS 24.0 for windows. The results in this study indicate that there is a correlation test that has been carried out there is a significant relationship between each gratitude (r -0.700 and p < .000) with psychological well-being (r -0.700 and p < .000). R square of 0.490 indicates that gratitude has an effect of 49% on psychological well-being. The remaining 51% of the percentage of the influence of the psychological welfare variable is influenced by other factors.